Aplicación de abonos orgánicos en el cultivo de manzanilla (matricaria chamomilla l.) en el recinto san vicente de la parroquia Puembo, cantón Pujilí. - Arias Jami, Damaris Rebeca (2023)
The main objective of the research project "Application of organic fertilizers in the cultivation of chamomile (Matricaria chamomilla L.) in San Vicente area, Puembo parish, Pujilí canton" was to apply organic fertilizers in the cultivation of chamomile (Matricaria chamomilla L. .) and to evaluate variables of growth, development, production of secondary metabolites (flavonoids) of the treatment that presents the highest yield and finally a cost-production analysis of the treatments under study. The experiment was carried out with a CRBD (completely randomized block design) applying three organic fertilizers at a dose of 7.8Kg/m2 (Pollinaza, Worm humus and biocompost), an absolute control without application, and chemical control at a dose of 5 74g/plant, all requirements calculated by soil analysis. In the variables studied, humus and biocompost, respectively, were predominant at 75 days T4 and T5, thus: plant height prevailed with 44.54cm and 43.75, the number of branches with 16.83, and 13.33 units, the number of inflorescences (flowers) with 17.66 and 16.16 units, fresh weight with 55.72g and 51.16g and dry weight of the plant with 12.83 and 11.16, % dry matter with 21.70 and 23.04%, yields with 3100Kg/ha and 2930Kg/ha, the production of flavonoids of T4 considered the best performance was 0.34% in relation to the control that was 0.24%. In the cost-benefit analysis, the most profitable projects were earthworm humus 61% of rentability.